Search Engine Optimization (SEO) for Journalistic Content in Building Brand Image for Innovation Products - Felicia Goenawan; Ido Prijana Hadi; Amelia Sidik (Scriptura, 2023)
The product innovations produced by Meal for 60+ focused on healthy food for the elderly. The purpose of Meal for 60+ is as a medium that can help everyone, be it mothers, fathers, teenagers, and children, in serving healthy food for the elderly at home. It is not easy for people to accept an innovative product. Companies must be able to build a Brand Image for their innovative products in the eyes of potential consumers. Therefore, the purpose of this research is to find out what factors are in the diffusion of innovative products and can be used to create messages on websites and Instagram. The paradigm in this research is positivistic with a quantitative approach and the research method used is a survey. The distribution of the questionnaire focused on respondents in Solo and Tulungagung. The results of this study indicate that Meal for 60+ should be more aggressive in conveying information related to their products. This is because respondents need acceptance from the surrounding community first before accepting innovative products. The keyword "healthy diet menu" is the main reference for respondents in searching for news. “HEREDITY.ID” will be one of the portal websites that can be accessed by the public, accommodates and becomes a source of detailed information on patent products in Indonesia.